Corrosion failures : theory, case studies, and solutions - Elayaperumal, K. 1937- (John Wiley & Sons, Inc., 2015)
Provides corrosion basics in a lucid manner to students and working professionals and over 80 corrosion-failure analysis case studies -Correlates Failure Analysis with Corrosion Science -Exclusively provides corrosion-related failure analysis case histories in one place in a convenient format -One-stop shop for both science and real time occurrence of the phenomenon of corrosion -Full coverage of all MOC, Materials of Construction, used for process equipments -Simple but Lucid presentation of Failure Analysis procedure.